Association of Mycobacterium avium subsp. paratuberculosis and SLC11A1 polymorphisms in Sardinian multiple sclerosis patients - Davide Cossu; Speranza Masala; Eleonora Cocco; Daniela Paccagnini; Stefania Tranquilli; Jessica Frau; Maria Giovanna Marrosu; Leonardo Antonio Sechi (Journal of Infection in Developing Countries)
Introduction: Recent findings propose that Mycobacterium avium subsp. paratuberculosis (MAP) infection could act as risk factor in favoring multiple sclerosis (MS) progression. SLC11A1 is a gene associated with mycobacterial survival in the host and it may be involved in the induction and maintenance of autoimmune disease.